Design of electrode configuration for in vitro experiments of epiretinal electrical stimulation of retinal ganglion cells. Issue 4 (1st July 2017) - Biswas, Satarupa; Das, Soumen; Mahadevappa, Manjunatha
Abstract : Progress in epiretinal prostheses needs attention towards the electrode tissue interface. A simulation study prior to biological evaluation can give an assessment of the spatial distribution of electrical and thermal parameters throughout the retinal tissue. The aim was to configure an electrode array that can elicit focal response in the tissue keeping charge density and heat produced within safety limits to avoid tissue damage. The AC/DC module and bioheat module of COMSOL Multiphysics 4.4 were used to numerically model the electrode tissue interface with different electrode size ranging from 10 to 500µm and configurations that are the best suit for in vitro experimental applications. Parameters like electric field, current density, potential, heat flux and temperature were evaluated. Electrodes having diameters 50–200µm produce steady and reproducible results with charge density and heat produced within safe limits. The configuration with a centre stimulating and surrounding alternating ground and recording electrodes arranged hexagonally could produce a focal response. The design of a multielectrode array is proposed which acts as a stimulator as well as a sensor for neural responses from isolated animal retina.